Nonaqueous Gel Casting of AlN Ceramics using Epoxy - Yixuan HE; Xiaohong WANG; Wenzhong LU (Medžiagotyra)
The AlN ceramics manufactured by a nonaqueous gel casting process were studied. It was shown that trimethylolpropane triglycidyl ether (TMPGE) and tetraethylenepentamine (TEPA) were suitable for the gel casting process through a nucleophilic addition reaction. This system cured at room temperature and avoided oxygen inhibition. The rheological behaviors of the slurries and bending strength of green bodies obtained under different conditions were investigated. Suspensions with a high-solid loading of 59 vol.% and low viscosity (678 mPa·s) were obtained with 1 wt.% dispersant, 20 wt.% TMPGE, and TEPA: TMPGE=1:5. The results showed that the bending strength of the green body is not only associated with the content of TMPGE, TEPA, and solid loading, but also the drying process. The bending strength greatly improved and reached 34.9 MPa after drying at 130 °C, which was strong enough for subsequent processing. With the increase of solid loading, sintered AlN ceramics exhibited higher relative density and thermal conductivity, reaching 99.6% and 152 W/(m·K) at 59 vol.%, while the optimized bending strength of 274 MPa was obtained at 55 vol.%. Meanwhile, complex-shaped ceramics without cracks were prepared.